A study on an unusual SN2 mechanism in the methylation of benzyne through nickel-complexation. Issue 39 (28th September 2017) - Hatakeyama, Makoto; Sakamoto, Yuki; Ogata, Koji; Sumida, Yuto; Sumida, Tomoe; Hosoya, Takamitsu; Nakamura, Shinichiro
Abstract : Joint research on the valence state of a benzyne–Ni complex (Ni 0 : η 2 -structure or Ni II : metallacycle) and the methylation with iodomethane. Abstract : In this study, three reaction mechanisms of a benzyne–nickel (Ni) complex ([Ni(C6 H4 )(dcpe)]) with iodomethane during the methylation process were investigated, namely (a) SN 2 reaction of the benzyne–Ni complex with iodomethane, (b) concerted σ-bond metathesis during the bond breaking/forming processes, and (c) oxidative addition of iodomethane to the Ni-center and the subsequent reductive elimination process. DFT calculations revealed that the reaction barrier of the SN 2 reaction is slightly lower than those of the other mechanisms. The results of orbital analyses suggest that [Ni(C6 H4 )(dcpe)] forms a metallacycle structure between benzyne and the Ni II (3d 8 ) center instead of the η 2 -structure with the Ni 0 (3d 10 ) center. The metallacycle structures became inappropriate as the intermediates of oxidative addition in the formation of the Ni II –Me bond, avoiding further oxidation to the high-valent Ni IV . The high free energy along σ-bond metathesis was generated from the steric hindrance, thus invoking methylation and Ni–I bond formation concertedly.